Cellular immunogenicity of human papillomavirus vaccines Cervarix and Gardasil in adults with HIV infection - Maria Zurek Munk-Madsen; Lars Toft; Tina Kube; Rolf Richter; Lars Ostergaard; Ole S. Søgaard; Martin Tolstrup; Andreas M. Kaufmann (Taylor & Francis Group, 2018)
Human papillomavirus (HPV) infection is a frequent cause of malignant and non-malignant disease, in particular among persons with HIV. HPV serotype-specific anti L1 antibodies protect against HPV infection but little is known about prophylactic HPV vaccine-induced cell-mediated immunity against HPV in high-risk individuals. We recently showed that both HPV vaccines (Gardasil® and Cervarix®) induce solid, serological immune responses in HIV-infected persons. This study aimed to characterize HPV-specific CD4 T cells in HIV-infected HPV-vaccine recipients, T cell responses being critical for B cell activation and antibody-isotype switching. Thirty HIV-infected patients on long-term antiretroviral treatment (ART) received 3 doses of either Cervarix (n = 15) or Gardasil (n = 15) vaccine at month 0, 1.5 and 6. Cryopreserved peripheral blood mononuclear cells (PBMC) from baseline, 7 and 12 months were subjected to 24-hour stimulation with specific pools of HPV L1-peptides (HPV6, 11, 16, 18, 31 and 45) and HPV E6/E7-peptide pools (HPV6/11 and HPV16/18). Fluorescence-activated cell sorting with intracellular staining (IC-FACS) against CD4, CD154, IL-2, and IFNγ was performed. Frequencies (%) of HPV-antigen specific CD4+ T cells (CD154+/IL-2+ or CD154+/ IFNγ+) were determined. Both HPV-vaccines significantly and comparably enhanced cell-mediated vaccine L1 antigen-specific immunity in HIV-positive adults receiving ART therapy at month 7 and 12 after first vaccine dose. This suggests that the vaccines induce CD4 T cellular memory despite HIV-induced immune compromisation.